2018
DOI: 10.1017/s0007485318000469
|View full text |Cite
|
Sign up to set email alerts
|

Effects of constant and fluctuating temperature on the development of the oriental fruit moth, Grapholita molesta (Lepidoptera: Tortricidae)

Abstract: The oriental fruit moth, Grapholita molesta, is an important pest in many commercial orchards including apple, pear and peach orchards, and responsible for substantial economic losses every year. To help in attaining a comprehensive and thorough understanding of the ecological tolerances of G. molesta, we collected life history data of individuals reared on apples under different constant temperature regimes and compared the data with moths reared under a variable outdoor temperature environment. Because G. mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the OFM, outliers had the strongest response to variables related to temperature followed by one variable related to precipitation and then another linked to temperature (Figure 5). Both species may therefore be under selection from variable temperatures as noted in biological studies (Chen et al, 2019; Zhang et al, 2016). However, the PFM pupates and often overwinters in the soil, while the OFM often pupates on trees (Yang et al, 2016; Zhang et al, 2016), which may explain the stronger impact of precipitation on the PFM than on the OFM.…”
Section: Discussionmentioning
confidence: 99%
“…In the OFM, outliers had the strongest response to variables related to temperature followed by one variable related to precipitation and then another linked to temperature (Figure 5). Both species may therefore be under selection from variable temperatures as noted in biological studies (Chen et al, 2019; Zhang et al, 2016). However, the PFM pupates and often overwinters in the soil, while the OFM often pupates on trees (Yang et al, 2016; Zhang et al, 2016), which may explain the stronger impact of precipitation on the PFM than on the OFM.…”
Section: Discussionmentioning
confidence: 99%
“…Pupal weight can be an indirect but easily measured index of fitness in Lepidoptera (Leuck and Perkins, 1972; Liu et al ., 2004; Chen et al ., 2019). Fecundity of insects is usually positively correlated with body size (Honěk, 1993; Nylin and Gotthard, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was suggested that developmental times were distinct between those predicted from constant temperatures and those under alternating temperatures around the same mean or natural fluctuating temperatures (Mironidis and Savopoulou-Soultani, 2008; Carrington et al ., 2013; Kjærsgaard et al ., 2013); therefore, life table studies under constant temperature are not realistic enough to reflect physiology under natural fluctuating conditions. Although increasing attention has been paid to life history traits under diurnal fluctuating temperatures, rarely have outdoor experiments been undertaken due to the inherent difficulties of field experiments (Tuan et al ., 2014; Chen et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…We created a physiological stage-structured model that incorporated the C. pomonella egg stage, five nondiapausing instar stadia (first-to-fifth), the diapausing fifth instar, pupae, reproductive adults, and senescent adults (Figure 1). We incorporated stage-specific vital rates that are dependent on ambient temperature as determined from previously published empirical work (Aghdam et al, 2009(Aghdam et al, , 2011Blomefield & Giliomee, 2009;Chen et al, 2019;Chidawanyika & Terblanche, 2011;Glenn, 1922;Graf et al, 2018;Howell & Neven, 2000;Howell & Schmidt, 2002;Khani & Moharramipour, 2010;Moffitt & Burditt, 1989;Neven, 2013;Setyobudi, 1989;Williams & McDonald, 1982;Yokoyama et al, 1987). The full model and its derivation are provided in Text S1, Figures S1-S3, and Table S1.…”
Section: Study Systemmentioning
confidence: 99%